Blater's power in local politics, village head election in Madura - Hidayaturrahman, Mohammad; Muhammad, Nur Shidqi; Tini, Dwi Listia Rika; Ubaid, Ahmad Hasan (Universitas Islam Malang, 2023)
The involvement of elite groups or certain groups in winning political contests is often carried out by candidates for political office. This also happens in local political contestations, village head elections. This research was conducted to reveal the role and behavior of blater in village elections in Sumenep, Madura, East Java. This research uses a descriptive qualitative model. The data collection technique was carried out using in-depth interviews with various informants involved in the election, such as blater, village head candidates and voters. Apart from that, document searches were also carried out regarding village election activities and after the election of the village head. To obtain accurate data, the research cross-checked the data collected, between the data obtained through in-depth interviews, and the documents traced and obtained by the researcher. From the research conducted, blater has an important role in the election of village heads. This is caused by several factors. Blater has influence, blater also has a strategy for carrying out his role, blater has certain preferences when the village head election takes place, and blater's role has an impact on the village head election process. Apart from that, the blater has a network that shapes the winning process.